Aplicación de medidas higiénicas en la preparación y expendio de alimentos ofertados por los trabajadores de la Asociación Divino Niño de la ciudad de Zamora, año 2015. - Campoverde Herrera, Vilma Soraya (2015)
The research aims to determine the application of hygienic measures in the preparation and sale of food offered by the workers of the Divine Child of the City Association of Zamora. The design was cross-sectional, descriptive, bibliographic, field and prospective.It was used like collection data tecnhique and the observation with their instruments, the Questionnaire and observation guide were applied to 37 vendors applied as data collection techniques. As resultadoib was obtained: the 54.05% are male, older than 30 years with 91.89% of mixed ethnicity with 91,89%, with a basic general education level of 51.35 %, on the application of sanitary measures 55% of street vendors not apply hygiene measures in the preparation and sale of food, such as factors influencing the non-application of hygienic measures is that 100% of the population does not have the current health card, the unavailability of water with 24.32% which is why the author implemented a nursing action plan aimed at improving the implementation of hygienic measures through educational, health and development, concluding street vendors do not apply hygiene measures in the preparation and sale of food with 55%, the main cause of non-application is the inappropriate use of clothing, hand washing, and a factor unavailability of water and photo no health effect as a requirement to verify the health status of the seller